Conservation resource allocation, small population resiliency, and the fallacy of conservation triage - David A. Wiedenfeld; Allison C. Alberts; Ariadne Angulo; Elizabeth L. Bennett; Onnie Byers; Topiltzin Contreras‐MacBeath; Gláucia Drummond; Gustavo A. B. da Fonseca; Claude Gascon; Ian Harrison; Nicolas Heard; Axel Hochkirch; et al. (Conservation Biology, 2021)
Some conservation prioritization methods are based on the assumption that conservation needs overwhelm current resources and not all species can be conserved; therefore, a conservation triage scheme (i.e., when the system is overwhelmed, species should be divided into three groups based on likelihood of survival, and efforts should be focused on those species in the group with the best survival prospects and reduced or denied to those in the group with no survival prospects and to those in the group not needing special efforts for their conservation) is necessary to guide resource allocation. We argue that this decision‐making strategy is not appropriate because resources are not as limited as often assumed, and it is not evident that there are species that cannot be conserved. Small population size alone, for example, does not doom a species to extinction; plants, reptiles, birds, and mammals offer examples. Although resources dedicated to conserving all threatened species are insufficient at present, the world's economic resources are vast, and greater resources could be dedicated toward species conservation. The political framework for species conservation has improved, with initiatives such as the UN Sustainable Development Goals and other international agreements, funding mechanisms such as The Global Environment Facility, and the rise of many nongovernmental organizations with nimble, rapid‐response small grants programs. For a prioritization system to allow no extinctions, zero extinctions must be an explicit goal of the system. Extinction is not inevitable, and should not be acceptable. A goal of no human‐induced extinctions is imperative given the irreversibility of species loss.

The matrix effect: how agricultural matrices shape forest fragment structure and amphibian composition - Lucas Ferrante; Fabricio Beggiato Baccaro; Eric Batista Ferreira; Maria Fernanda de Oliveira Sampaio; Thays Santos; Rodrigo Cesário Justino; Ariadne Angulo (Journal of Biogeography, 2017)
Aim Habitat loss and fragmentation are considered the main drivers of species population declines and extinctions in the world. The large‐scale replacement of natural habitats with human‐modified habitats, such as the replacement of forests with agricultural and livestock farming areas, creates a scenario where natural habitat patches are immersed in an inhospitable land use matrix. We sought to evaluate how forest fragments (FFs) are influenced by the different surrounding landscape components, where we assessed how agricultural matrices that differ in structure and seasonality affect the structure of FFs and their amphibian assemblages. Location Atlantic Forest, Brazil. Methods Using diverse methods including satellite imagery, historical land use and field data, we evaluated the effects of representative agricultural matrices on the structure of FFs and their amphibian composition, species richness and abundance. Results Our results suggest that the structure of FFs and amphibian composition, species richness and individual abundance are intimately linked to the type of matrix and its proportion around FFs. The nature of the matrix is more likely to affect species richness, individual abundance and composition of amphibian assemblages than FF size, reducing the species‐area relationship in FFs. There is strong support for the hypothesis that certain agricultural matrices facilitate FF exposure to the elements and a decrease in forest integrity within the fragment, which is reflected in a loss of strict forest inhabitants. Those matrices that allow for a greater exposure of FFs also appear to favour their occupation by habitat generalists. Main conclusions Surrounding matrices affect the structure and dynamics of forest remnants and should therefore be considered in management plans of severely fragmented landscapes. The influence of the land matrix should be urgently assessed, as it has effects on species occurrences and distribution. This is especially relevant considering the increasing deforestation rates in biodiversity hotspots world‐wide.

An evaluation of the robustness of global amphibian range maps - Gentile Francesco Ficetola; Carlo Rondinini; Anna Bonardi; Vineet Katariya; Emilio Padoa‐Schioppa; Ariadne Angulo (Journal of Biogeography, 2014)
Aim Maps of species ranges are among the most frequently used distribution data in biodiversity studies. As with any biological data, range maps have some level of measurement error, but this error is rarely quantified. We assessed the error associated with amphibian range maps by comparing them with point locality data. Location Global. Methods The maps published by the Global Amphibian Assessment were assessed against two data sets of species point localities: the Global Biodiversity Information Facility ( GBIF ), and a refined data set including recently published, high‐quality presence data from both GBIF and other sources. Range fit was measured as the proportion of presence records falling within the range polygon(s) for each species. Results Using the high‐quality point data provided better fit measures than using the raw GBIF data. Range fit was highly variable among continents, being highest for North American and European species (a fit of 84–94%), and lowest for Asian and South American species (a fit of 57–64%). At the global scale, 95% of amphibian point records were inside the ranges published in maps, or within 31 km of the range edge. However, differences among continents were striking, and more points were found far from range edges for South American and Asian species. Main conclusions The Global Amphibian Assessment range maps represent the known distribution of most amphibians well; this study provides measures of accuracy that can be useful for future research using amphibian maps as baseline data. Nevertheless, there is a need for greater investment in the continuous updating and improvement of maps, particularly in the megadiverse areas of tropical Asia and South America.

Cryptic species complexes, widespread species and conservation: lessons from Amazonian frogs of the Leptodactylus marmoratus group (Anura: Leptodactylidae) - Ariadne Angulo; Javier Icochea (Systematics and Biodiversity, 2010)